Alzheimer’s Transgenic Model Is Characterized by Very Early Brain Network Alterations and β-CTF Fragment Accumulation: Reversal by β-Secretase Inhibition - Mondragón-Rodríguez, Siddhartha; Gu, Ning; Manseau, Frederic; Williams, Sylvain (Frontiers in Cellular Neuroscience, 2018)
Alzheimer’s disease (AD) is defined by the presence of amyloid-β (Aβ) and tau protein aggregates. However, increasing data is suggesting that brain network alterations rather than protein deposition could account for the early pathogenesis of the disease. In the present study, we performed in vitro extracellular field recordings in the CA1/subiculum area of the hippocampus from 30 days old J20-TG-AD mice. Here, we found that theta oscillations were significantly less rhythmic than those recorded from control group. In addition, J20 mice displayed significantly less theta-gamma cross-frequency coupling (CFC) as peak modulation indexes for slow (25–45 Hz) and fast (150–250 Hz) gamma frequency oscillations were reduced. Because inhibitory parvalbumin (PV) cells play a vital role in coordinating hippocampal theta and gamma oscillations, whole-cell patch-clamp recordings and extracellular stimulation were performed to access their intrinsic and synaptic properties. Whereas neither the inhibitory output of local interneurons to pyramidal cells (PCs) (inhibitory→PC) nor the excitatory output of PCs to PV cells (PC→PV) differed between control and J20 animals, the intrinsic excitability of PV cells was reduced in J20 mice compared to controls. Interestingly, optogenetic activation of PV interneurons which can directly drive theta oscillations in the hippocampus, did not rescue CFC impairments, suggesting the latter did not simply result from alteration of the underlying theta rhythm. Altered young J20 mice was characterized by the presence of β-CTF, but not with Aβ accumulation, in the hippocampus. Importantly, the β secretase inhibitor AZD3839-AstraZeneca significantly rescued the abnormal early electrophysiological phenotype of J20 mice. In conclusion, our data show that brain network alterations precede the canonical Aβ protein deposition and that, such alterations can be related to β-CTF fragment.